Effects of seeding rates and harvest date on forage yield and nutritive value of pea-triticale intercropping - Pereira-Crespo S.; Fernández-Lorenzo B.; Valladares J.; González-Arráez A.; Flores G. (The contributions of grasslands to the conservation of Mediterranean biodiversity, 2010)
In recent years the intensification in the forage production of dairy farms in Galicia (Northwest Spain) has led to the need of an alternative to Italian ryegrass as an annual winter crop in rotation with maize. The reasons were: the low content in protein and the harvesting costs of Italian ryegrass. In the region, the intercropping of pea (Pisum sativum L.) with triticale (x Triticosecale Witt.) was suggested as a potential alternative. The objective of this research was to evaluate the effects over forage yields and nutritive value of the seeding rate of pea:triticale (200:0, 150:75, 100:150, 50: 225 and 0:300 seeds m-2) and harvest date (middle of April and middle of May), to determine the most appropriate mixture and the optimal harvest date. The highest contents of crude protein (CP) were obtained in the first harvest date. Pea monoculture provided the highest CP (18.5 percent dry matter), followed by the mixture with seeding ratio 150:75. In contrast, triticale monocultures had the lowest CP. The increase of pea seeding ratio proportion in mixture increased crude protein and decreased neutral detergent fiber. The first harvest date was the optimal, according to protein content, although dry matter yields were lower.
13. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM International Network for the Research and Development of Pasture and Forage Crops, 2010/04/07-10, Alicante (Spain)